Adam Saks - Blüdnikow, Bent (Rambam. Tidsskrift for jødisk kultur og forskning, 2013)
Adam Saks - A Danish Artist in Berlin Adam Saks is a successful Danish artist living and working in Berlin. His works have been exhibited at galleries and museums across Europe, recently at Kiasma Museum of Contemporary Art in Helsinki. Saks was a student at The Royal Danish Academy of Fine Arts in Copenhagen from 1993-1999, and shortly after finishing his studies, he moved to Berlin, a Mecca of modern art and home to what could be called a dark Berlin-style. Saks, however, does not consider himself to be part of a movement or style, although he acknowledges an admiration for pop-artists like Andy Warhol. The colourful paintings are full of symbols and figures, eroticism, humour, and beauty. The artist says that his paintings are meant to pass on emotions, not political, ideological or moral agendas. It is up to the viewer to make their own interpretations. Saks is interested in tattoos, and a series of his paintings are male torsos with different tattoos - many of them with masculine symbols and writings. Another series of paintings are full of flowers and oriental characters. The works of Adam Saks are rich and colourful and keep the viewer amazed and amused. Rambam is proud to present to its readers a collection of Adam Saks' paintings.